Understanding Multi-Cloud and Hybrid Cloud Architectures in Data Management - Prashanth Reddy Kora (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the growing adoption of multi-cloud and hybrid cloud architectures in modern data management practices. It delves into the benefits, challenges, and best practices associated with these complex cloud strategies. The article presents key statistics and projections from industry leaders, highlighting the rapid growth and increasing importance of multi-cloud and hybrid cloud solutions. It discusses how these architectures enhance data redundancy, vendor flexibility, cost optimization, and performance while addressing critical issues such as data sovereignty, scalability, and legacy system integration. The piece also examines the challenges organizations face in implementing these strategies, including data integration, security, skill gaps, compliance, and cost management. Finally, it outlines best practices for effective implementation, emphasizing the need for comprehensive data governance, robust integration tools, cloud-agnostic technologies, and continuous optimization.